KULTURSPEZIFISCHES WISSEN IN DER INTERKULTURELLEN ALLTAGSKOMMUNIKATION IM BERUF. EINE KOMPARATIVE STUDIE AUS DER PERSPEKTIVE DER STUDENT/-INNEN DER UNIVERSITÄT POLITEHNICA TIMIŞOARA, ÜBERSETZUNGSWISSENSCHAFTEN VERSUS INGENIEURWISSENSCHAFTEN (COMPUTER SCIENCE). - RUTHNER, Andreea Rodica (Studii de Ştiintă şi Cultură, 2024)
In the age of globalization, our students of both, Translation Studies and Computer Engineering, will be working very soon and to a very high percentage in international companies and intercultural teams. Therefore, we believe that culture-specific knowledge, intercultural awareness, a careful attitude towards differences and qualitative information processing, in summary: intercultural mindfulness, are essential in achieving professional success. This thought raises, however, the question if and how aware of these aspects of their future professional life our students are. How important is it to them to communicate, to understand and to act successfully in a multicultural working community, or, in other words, to master linguistic and cultural understanding and acting with confidence?